Study of the Complex Stiffness of a Vibratory Mechanical System with Shape Memory Alloy Coil Spring Actuator - Samuell A. Holanda; Antonio A. Silva; Carlos J. de Araújo; Alberdan S. de Aquino (Shock and Vibration)
The vibration control is an important area in the dynamic of structures that seeks to reduce the amplitude of structural responses in certain critical frequency ranges. Currently, the scientific development leads to the application of some actuators and sensors technologically superior comparing to the same features available on the market. For developing these advanced sensors and actuators, smart materials that can change their mechanical properties when subjected to certain thermomechanical loads can be employed. In this context, Shape memory alloys (SMAs) may be used for developing dynamic vibration dampers which are capable of acting on the system providing proper tuning of the excitation frequency and the natural frequency. This paper aims to analyze the behavior of the stiffness and damping of a SMA helical coil spring actuator coupled to a mechanical system of one degree of freedom (1 DOF) subjected to an unbalanced excitement force and a temperature control system. By analyzing the effect of these parameters on the structural response and considering the concept of complex stiffness, it can be possible to predict the system's behavior within certain acceptable ranges of vibration, already in the design phase.